Identification of capillary rarefaction using intracoronary wave intensity analysis with resultant prognostic implications for cardiac allograft patients. (13th December 2017) - Broyd, Christopher J; Hernández-Pérez, Francisco; Segovia, Javier; Echavarría-Pinto, Mauro; Quirós-Carretero, Alicia; Salas, Clara; Gonzalo, Nieves; Jiménez-Quevedo, Pilar; Nombela-Franco, Luis; Salinas, Pablo; Núñez-Gil, Ivan; Del Trigo, Maria; et al.
Abstract: Aims: Techniques for identifying specific microcirculatory structural changes are desirable. As such, capillary rarefaction constitutes one of the earliest changes of cardiac allograft vasculopathy (CAV) in cardiac allograft recipients, but its identification with coronary flow reserve (CFR) or intracoronary resistance measurements is hampered because of non-selective interrogation of the capillary bed. We therefore investigated the potential of wave intensity analysis (WIA) to assess capillary rarefaction and thereby predict CAV. Methods and results: Fifty-two allograft patients with unobstructed coronary arteries and normal left ventricular (LV) function were assessed. Adequate aortic pressure and left anterior descending artery flow measurements at rest and with intracoronary adenosine were obtained in 46 of which 2 were lost to follow-up. In a subgroup of 15 patients, simultaneous RV biopsies were obtained and analysed for capillary density. Patients were followed up with 1–3 yearly screening angiography. A significant relationship with capillary density was noted with CFR ( r  = 0.52, P  = 0.048) and the backward decompression wave (BDW) ( r  = −0.65, P  < 0.01). Over a mean follow-up of 9.3 ± 5.2 years patients with a smaller BDW had an increased risk of developing angiographic CAV (hazard ratio 2.89, 95% CI 1.12–7.39; P  = 0.03). Additionally, the index BDW was lower in those who went on to have a clinical CAV-events ( P  = 0.04) as well as more severe disease ( P  = 0.01). Conclusions: Within cardiac transplant patients, WIA is able to quantify the earliest histological changes of CAV and can predict clinical and angiographic outcomes. This proof-of-concept for WIA also lends weight to its use in the assessment of other disease processes in which capillary rarefaction is involved.